2001
DOI: 10.1128/jb.183.16.4737-4746.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of VPI Pathogenicity Island and CTXφ Prophage in Environmental Strains of Vibrio cholerae

Abstract: Environmental isolates of Vibrio cholerae of eight randomly amplified polymorphic DNA (RAPD) fingerprint types from Calcutta, India, that were unusual in containing toxin-coregulated pilus or cholera toxin genes but not O1 or O139 antigens of epidemic strains were studied by PCR and sequencing to gain insights into V. cholerae evolution. We found that each isolate contained a variant form of the VPI pathogenicity island. Distinguishing features included (i) four new alleles of tcpF (which encodes secreted viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 53 publications
9
117
0
Order By: Relevance
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 82%
“…However, our results contradict the assumption that most cholera toxin-producing strains are also positive for TCP, since TCP is known to be the receptor for CTXφ infection of V. cholerae. In fact, our results appear to be consistent with data from recent studies that report the presence of the two virulence genes found in epidemic strains, ctxAB and tcpA, in environmental and clinical strain of serogroups other than O1 and O139 5,10,27,28,31,32 .…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have suggested a role of virulence factors or their homologues in the symbiotic association of V. cholerae with a variety of aquatic organisms. Besides gene clusters associated with pandemic strains, recent studies have recognized the existence of different alleles of virulence genes in environmental V. cholerae strains, including different alleles of tcpA, tcpF, and toxT genes and different alleles of the CTX⌽ prophage repressor rstR in vibrios of various nonepidemic serogroups (9,10). It has been suggested that the different environmental alleles of virulence genes may have evolved in response to selective pressures that vary between the environment and the host (36).…”
Section: Discussionmentioning
confidence: 99%
“…Included were 15 strains that colonized mice and caused fluid accumulation in rabbits despite the absence of TCP and CT genes. Recent studies have identified genetic variants of tcpA gene encoding the major pilus subunit in environmental strains (9). These 15 strains were also negative for the known environmental variants of tcpA gene.…”
Section: Environmental V Cholerae Strains Carry Diverse Combinations Ofmentioning
confidence: 99%
See 2 more Smart Citations